Shape optimization of tooth profile of a flexspline for a harmonic drive by finite element modelling - Kayabasi, Oguz; Erzincanli, Fehmi (Elsevier Sci Ltd, 2007)
Analytical procedures often fail to predict correctly the maximum stress and its position, a new, more reliable method is needed for that purpose. A computational stress-strain analysis of the flexible gear, based on the finite element method, is investigated as an alternative and is presented here. The aim of this study was to calculate the stress on flexspline teeth and find optimum shape of teeth to maximize fatigue life. Finite element analysis of the harmonic drive flexspline shows that the numerical analysis provides better estimate of the maximum stress than the experimental procedures. This leads to the conclusion that only the proposed numerical procedure should be used when designing the flexspline. The presented approach to a stress-deformation analysis of the flexspline can help the designer to accurately determine the maximum stress on the flexspline, which can then be used for optimizations of the flexspline construction. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: fatigue; elastic behavior; harmonic drive; flexspline; optimization